Effects of Sub Chronic Exposure of Diazinon on Wild Pigeon (Culumba livia gaddi) at Basrah City/Southern Iraq - Al-Sereah , Bahaa A. (International Journal of Poultry Science, 2012)
A three months as sub chronic study of diazinon on male wild pigeons (Culumba livia gaddi) by oral intubation were done. The study consisted of four groups each with six pigeons: A(high dose 0.3 mg), B(intermediate dose of 0.6 mg), C(low dose 1.2 mg) and D(untreated control). Clinical observation of treated pigeons did not show significant changes only the birds appeared to the quite after dosing for short time.